Odpowiedzi

2010-01-27T16:28:17+01:00
A) (4a – 2b) – 6a – (7b -8) =
= 4a-2b-6a-7b+8 =
= -2a-2b+8 =
= -2*1 - 2*(-1)+8 =
= -2+2+8 = 8

b) 3a – (4b + 18) + 5a + 9=
= 3a-4b-18+5a+9 =
= 8a-4b-9 =
= 8*1 - 4*(-1)-9 =
= 8+4-9 = 3

c) 5a – (4a2 + b – a) + (a2 – 7) =
= 5a-4a²-b+a+a²-7 =
= 6a-3a²-b-7 =
= 6*1 - 3*1²-(-1)-7 =
= 6 - 3 + 1 - 7 = -3
2010-01-27T16:31:02+01:00
A) (4a – 2b) – 6a – (7b -8) =4a-2b-6a-7b+8=-2a-9b+8=-2*1-9*(-1)+8=
=-2+9+8=15
b) 3a – (4b + 18) + 5a + 9=3a-4b-18+5a+9=8a-4b-9=8+4-9=3
5a – (4a2 + b – a) + (a2 – 7) = 5a-4a²-b+a+a²-7= 6a-3a²-b-7 = 6*1 - 3*1²-(-1)-7 =6-3+1-7=-3